Biblioterapi Dan Stres : Study Kasus Pasca Vonis Narapidana Wanita: Biblioterapi Dan Stres : Study Kasus Pasca Vonis Narapidana Wanita - wibianti, Lutvia; Ahmad Syamsul Muarif (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
Female prisoners often experience post-sentence psychological distress influenced by social stigma, family responsibilities, and past trauma. This condition can worsen their mental health and hinder their social reintegration process. This study aims to analyze the role of bibliotherapy in helping to relieve stress in post-conviction women prisoners, by exploring the impact of reading therapy on their psychological recovery process. The research used a qualitative approach with a case study design. The research was conducted at Class II A Banyuwangi Correctional Facility, focusing on post-conviction stressed female prisoners with human trafficking cases. Data collection techniques were carried out through in-depth interviews with counselees and correctional institution officers, observations made in the prison environment, and documentation. The data analysis technique in this study uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results of Islamic teachings-based counseling with al-qur'an reading bibliotherapy techniques can increase the spiritual strength of the counselee, help accept life trials with patience and tawakal through consistent spiritual routines, which act as emotional therapy, and form a more mature character, and prepare for the future with a calm and constructive soul.